Canagliflozin combined with metformin versus metformin monotherapy for endocrine and metabolic profiles in overweight and obese women with polycystic ovary syndrome: A single-center, open-labeled prospective randomized controlled trial - Zhang, Jiaqi; Xing, Chuan; Cheng, Xiangyi; He, Bing (Frontiers in Endocrinology, 2022)
Objectives: Canagliflozin (CANA), a kind of sodium-glucose cotransporter-2 (SGLT-2) inhibition, study in which the role of CANA monotherapy in polycystic ovary syndrome (PCOS) has been investigated, and it could become a novel option in the PCOS treatment. Nevertheless, trials focused on SGLT-2 combination therapy’s efficacy, and safety in PCOS patients are limited. This randomized controlled trial compared the efficacy and safety of CANA and metformin (MET) combination therapy and MET monotherapy in endocrine and metabolic profiles of overweight and obese women with polycystic ovary syndrome (PCOS). Methods: Fifty-one overweight or obese non-diabetic PCOS women between 18 and 40 years old were enrolled. Patients were randomly allocated to receive either CANA/MET or MET treatment. The CANA/MET group received CANA 100 mg once daily plus MET 1000 mg twice daily, while the MET group received MET 1000 mg twice daily for three months. Changes in menstrual pattern, anthropometric parameters, gonadal parameters, glucose and lipid homeostasis, and adverse events (AEs) were evaluated. Results: Compared with the MET group, women have a significantly lower level of total testosterone (TT), area under the curve for glucose (AUCGlu), and area under the curve for insulin (AUCIns) to AUCGlu ratio in the combination group. There were no significant differences in menstrual frequency, body weight, body mass index, follicle-stimulating hormone, luteinizing hormone, free androgen index, sex hormone-binding globulin, androstenedione, fasting blood glucose, fasting insulin, AUCIns, homeostasis model assessment-insulin resistance (HOMA-IR), triglycerides, total cholesterol, low-density lipoprotein cholesterol, apolipoprotein A1 (Apo A1), apolipoprotein B (Apo B), and APO B/A1 ratio. AEs were seen in 57.70% (15/26) and 68.00% (17/25) of patients in the CANA/MET and MET groups, respectively. Conclusions: In overweight and obese women with PCOS, CANA and MET combination therapy may be similar to MET monotherapy in improving menstrual frequency, weight control, hyperandrogenemia, and relieving insulin resistance. CANA/MET may have more benefits in reducing TT, AUCGlu, and the AUCIns/AUCGlu ratio within three months than MET monotherapy. Trial registration: ClinicalTrials.gov, NCT04973891.